Hubungan Pendidikan Kewirausahaan dan Minat Berwirausaha Terhadap Sikap Kewirausahaan Mahasiswa Fakultas Ekonomi Universitas Negeri Makassar - Syahruddin, Nilam Cahya; Azis, Muhammad; Inanna, Inanna (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
The purpose of this study was to find out the description of entrepreneurship education and entrepreneurial interest in Economic Faculty students of Makassar State University a partially and simultaneously. Data collection techniques are carried out through questionnaire techniques and documentation. Data analysis techniques are Normality Test, Linearity Test, Multiple Correlation Â Analysis, Bivariate, and F Test. The results showed that partially and simultaneously entrepreneurship education and entrepreneurial interest have a significant relationship to the entrepreneurial attitudes of students of the Economic Faculty of Makassar State University